Introducing an Organ Donor Registry in Saskatchewan - Amy Zarzeczny; Luiza Radu (McMaster University Library Press, 2021)
On 3 September 2020, Saskatchewan launched an organ donor registry that allows participants 16 years and older to register their intent to be an organ donor either online or using a paper form. Saskatchewan has historically performed poorly at a national level with low rates of organ donations. Saskatchewan's new registry is intended to increase the numbers of organ donors in the province, while also helping to modernize its organ donation system and ease donation conversations with families. Saskatchewan's introduction of this registry brought the province in line with other provinces and territories across Canada that use similar systems, and provided a response to the surge in public interest around organ donation that followed the Humboldt Bronco bus crash tragedy and related "Logan Boulet Effect." The 2019-2020 and 2020-2021 provincial budgets included dedicated funding for the development and launch of the registry, which was accompanied by a media campaign to increase public awareness. Though it is too early to evaluate the success of the registry, early indications suggest donation rates will be a key evaluation metric. Registries are commonly thought to help increase public awareness of, and support for, organ donation, but improving Saskatchewan's organ donation rates will likely also require companion measures to strengthen the culture and practice of donation in the province. Le 3 septembre 2020, la province de Saskatchewan a mis en place un registre des donneurs d'organes qui permet aux participants âgés de 16 ans et plus d'enregistrer, en ligne ou sur papier, leur intention d'être un donneur d'organes. Le taux de dons d'organes a été toujours été bas en Saskatchewan comparé au niveau national. Le nouveau registre de la province vise à accroître le nombre de donneurs d'organes tout en aidant à moderniser le système de dons d'organes et à faciliter les discussions sur le don avec les familles. L'introduction de ce registre en Saskatchewan a mis la province sur la même ligne que les provinces et territoires qui utilisent un système comparable, et a fourni une réponse à l'intérêt croissant du public pour le dons d'organes à la suite de l'accident de bus des Broncos de Humboldt et de l'Effet Logan Boulet qui la suivi. Les budgets provinciaux pour 2019-20 et 2020-21 ont alloué des fonds pour le développement et le lancement du registre, qui a été accompagné d'une campagne d'information visant à le rendre visible au public. Bien qu'il soit trop tôt pour évaluer le succès du registre, il est clair que le taux de don d'organes sera une mesure clé de l'évaluation. Les registres sont souvent vus comme des outils pour augmenter la visibilité et le soutien public au don d'organes, mais afin d'améliorer le taux de don d'organes en Saskatchewan, il faudra sans doute aussi des mesures d'accompagnement pour renforcer la culture et la pratique du don d'organes dans la province.